Solution-plasma-induced oxygen vacancy enhances MoOx/Pt electrocatalytic counter electrode for bifacial dye-sensitized solar cells - Li, Yanan; Wang, Yinglin; Lin, Jianfei; Shi, Yuming; Zhu, Kuangyu; Xing, Yanmei; Li, Xiaofei; Jia, Yuwen; Zhang, Xintong (Frontiers in Energy Research, 2022)
Bifacial dye-sensitized solar cells (DSCs), harvesting light from both front and rear sides, are potential high-efficiency photovoltaic devices with broad application environments. The electrocatalytic counter electrodes (CEs) of bifacial DSCs could determine the light-harvesting from the rear side and the charge collection of solar cells through electrocatalytic processes. As a result, high-activity and high-transparency CEs are essential for bifacial DSCs. Recently, novel CEs based on strong metal-support interaction (SMSI) have been proved to improve catalytic and stability of the metal catalytic sites and induce great efficiency increase of bifacial DSCs. However, the contradiction between the transparency and conductivity of support is still a major challenge for the application of SMSI-based CEs on bifacial DSCs. Herein, we utilized a solution plasma (SP) method to introduce oxygen vacancies into a transparent MoO3 support film. These SP-induced oxygen vacancies improved the conductivity of MoO3 and the interaction between the metal Pt catalytic sites and support, thereby enhancing the catalytic activity and transparency of MoO3/Pt CEs. Consequently, the bifacial DSCs with MoO3/Pt CEs yielded a high efficiency of 7.56% and 6.41% with the front- and rear-side illumination, respectively. This impressive front-to-rear efficiency ratio of 85% indicated that the SP method has a positive effect to construct high-performance CEs and other electrocatalysis materials based on SMSI.